Intravenous tranexamic acid and intraoperative visualization during functional endoscopic sinus surgery: a double‐blind randomized controlled trial. Issue 4 (8th October 2012) - Langille, Morgan A.; Chiarella, Angelo; Côté, David W.J.; Mulholland, Graeme; Sowerby, Leigh J.; Dziegielewski, Peter T.; Wright, Erin D.
<x xml:space="preserve">Abstract</x> Background Bleeding during endoscopic sinus surgery (ESS) can hinder surgical progress and may be associated with increased complications. Tranexamic acid is an antifibrinolytic that is known to reduce operative bleeding. The current study was designed to assess the effect of adjunctive intravenous tranexamic acid on intraoperative bleeding and the quality of the surgical field during ESS. Methods Double‐blind, randomized, controlled trial. Patients undergoing ESS for the primary diagnosis of chronic rhinosinusitis with or without polyposis were included. Sample size calculation based on a clinically relevant difference in the Wormald surgical field score yielded a sample of 28. In addition to standard measures to minimize blood loss, study patients received intravenous tranexamic acid with control patients receiving intravenous normal saline. Outcome measures included the Wormald grading scale to assess the intraoperative surgical field and estimated blood loss based on suction container contents with irrigation fluid subtracted. Results Twenty‐eight patients (median age, 45 years; range, 23–80 years) were included in the study. Diagnoses included chronic rhinosinusitis without polyposis (n = 5), chronic rhinosinusitis with polyposis (n = 23). The use of the tranexamic acid was not associated with a statistically significant decrease in estimated blood loss (201 vs 231 mL; p = 0.60) or Wormald grading scale (5.84 vs 5.80; p = 0.93). There were no adverse events or complications during the study. Conclusion Adjunctive intravenous tranexamic acid does not appear to result in a clinically meaningful reduction in blood loss or improve visualization of the surgical field during ESS.